The Effect Of Workload, Self Efficacy On Burnout Among Madrasah Operators In Dapodik Applications In Bireun District - Sullaida, Sullaida; nurmala, nurmala (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
the purpose of the study was to analyze the effect of workload and self-efficacy on burnout among Madrasah operators on dapodik applications in Bireun Regency. The data analysis method used was multiple linear regression analysis. The number of respondents is 54 Madrasah operators, using probably sampling technique with simple random sampling. Hypothesis testing using a partial test and a partial simultaneous test partially positive and significant effect on workload on burnout of Madrasah operators on dapodik applications in Bireuen Regency, and self-efficacy negatively affects burnout among Madrasah operators on dapodik applications in Bireun Regency. Workload and self-efficacy affect burnout among Madrasah operators on dapodik applications in Bireun Regency. It is expected that Madrasah operators perceive their work not as a burden, so operators can work more comfortably and prevent burnout. Operators among Madrasahs in Bireun Regency have high enough self-efficacy, in order to maintain or increase their current self-efficacy, so that burnout is getting smaller. Keywords : workload, self efficacy, burnout.